Chemical routes for synthesis of polypyrrole–based nanocomposites incorporating graphene platelets from natural Shungite. (2019) - Politi, Sara; Tamburri, Emanuela; Carcione, Rocco; Angjellari, Mariglen; Lazzarini, Laura; Letizia Terranova, Maria
Abstract: Polypyrrole (PPy)-based nanocomposites are synthesized by a micro-emulsion oxidative chemical polymerization of pyrrole monomer. Graphene platelets (GP), extracted from Shungite mineral powders through innovative procedures, are used as nanoinclusions to enhance the interesting properties of the pure polymer. SEM and HR-TEM analyses evidence that diverse PPy nanostructures are obtained in the presence of different dopant surfactants: globular grains with sodium dodecyl sulfate (SDS) anionic surfactant, and tubular features with hexadecyltrimethylammonium bromide (CTAB) cationic surfactant. Raman spectroscopy reveals that the polymer chains are in a semi-oxidized state. Functional characterizations evidence that the PPy-based nanocomposites doped with SDS are characterized by improved charge transport properties.